PLA-THF-PEG nanoparticles Co-encapsulating AV3 and KH3 for synergistic pancreatic cancer therapy via stromal remodeling and metabolic inhibition - Liu, Xiaorong; Hu, Yuanmin; Yu, Jiaqi; Xue, Yuzhe; He, Xuesong; Jiang, Fenfen (Frontiers in Pharmacology, 2026)
IntroductionPancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies, characterized by dense desmoplastic stroma, metabolic reprogramming, and poor therapeutic response. Stromal desmoplasia limits drug penetration, while glycolytic adaptation supports tumor progression. Effective strategies that simultaneously target stromal barriers and tumor metabolism are urgently needed.MethodsTo overcome these challenges, we developed a dual-targeted, pH-responsive nanoplatform (PLA–THF–PEG/AV3/KH3 nanoparticles, termed AKNPs) that co-delivers AV3, a peptide antagonist of integrin α5 (ITGA5), and KH3, an allosteric inhibitor of phosphoglycerate mutase 1 (PGAM1). AKNPs were prepared by self-assembly and characterized for morphology, colloidal stability, and pH-triggered disassembly under acidic conditions mimicking tumor and endo/lysosomal environments. In vitro and in vivo therapeutic evaluations were performed using PANC-1 models.ResultsAKNPs exhibited uniform spherical morphology, excellent colloidal stability, and pH-sensitive disassembly. In vitro, AKNPs showed superior cytotoxicity in PANC-1 cells compared with free AV3 or AV3+KH3, accompanied by downregulation of fibrosis markers (α-SMA, COL1A1), metabolic regulator PGAM1, ITGA5, and immune checkpoint PD-L1, indicating combined stromal-remodeling and immunomodulatory effects. In vivo, in a PANC-1 xenograft model, AKNPs significantly inhibited tumor growth compared with PBS, AV3, or AV3+KH3. Tumor volumes and weights were reduced, and histological analyses revealed decreased fibrosis, lower tumor density, and enhanced necrosis. Western blot analysis of tumor tissues confirmed suppression of α-SMA, COL1A1, ITGA5, PGAM1, and PD-L1.DiscussionThese findings demonstrate that pH-sensitive AKNPs integrate stromal remodeling and metabolic inhibition to synergistically suppress PDAC progression. This nanoplatform provides a promising therapeutic strategy for overcoming stromal and metabolic barriers in pancreatic cancer and may serve as a foundation for future combination regimens.